A rapid synthesis of the evidence on interventions supporting self-management for people with long-term conditions : PRISMS - Practical systematic Revlew of Self-Management Support for long-term conditions /: PRISMS - Practical systematic Revlew of Self-Management Support for long-term conditions. (December 2014) - Taylor, Stephanie J. C
No abstract available